2011
DOI: 10.1089/pho.2010.2896
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Phototherapy (λ660 nm) on the Outcome of Oral Chemical Carcinogenesis on the Hamster Cheek Pouch Model: Histological Study

Abstract: It is concluded that LLLT, within the parameters used in the present study, caused a significant progression of the severity of SCC in the oral cavity of hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…These results are in line with previous performed studies. The study of de C. Monteiro et al (21) showed in vivo progression after LLLT (56.4 J/cm2) of chemically induced squamous cell carcinoma, in the oral cavity of hamsters. Gomes Henriques et al reported increased proliferation and invasion properties of SCC cells irradiated with LLLT at low energy densities (0.5 and 1 J/cm2) in a dose and time-dependent manner (17).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous performed studies. The study of de C. Monteiro et al (21) showed in vivo progression after LLLT (56.4 J/cm2) of chemically induced squamous cell carcinoma, in the oral cavity of hamsters. Gomes Henriques et al reported increased proliferation and invasion properties of SCC cells irradiated with LLLT at low energy densities (0.5 and 1 J/cm2) in a dose and time-dependent manner (17).…”
Section: Discussionmentioning
confidence: 99%
“…19 In the present study, the sessions took place twice a week for 6 weeks, with the objective of keeping a steady cell response and maintaining the patients' adherence to therapy. Furthermore, as some authors mention that LLLT can stimulate not only the healthy cells but also the tumor cells, [41][42][43] during LLLT applications, the areas close to the already-treated tumor lesions were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT is considered to be a non-ionizing irradiation that is not able to induce damage to cells’ DNA; however, it can modify cell behavior [23, 28, 29], and that is why LLLT is generally counter-indicated for proliferating or dysplastic lesions that can potentially turn into neoplasia [19, 30]. Besides, in vitro cultured cancer cells may not represent the complex biological environment found in a tumor growing in its host [31, 32]; however, cell culture is the safest and simplest way of searching for possible cell growth and increased invasion produced by the modulation of specific signaling pathways.…”
Section: Discussionmentioning
confidence: 99%